Advances in bromine speciation in volcanic plumes - Gutmann, Alexandra; Bobrowski, Nicole (Frontiers in Earth Science, 2018)
Volcanoes are a significant halogen source to the atmosphere. After water, carbon dioxide and sulfur compounds, halogens are often the most abundant gases in volcanic plumes. In the past, less attention was given to the heavy halogens bromine and iodine. However, the discovery of bromine monoxide (BrO) in volcanic plumes led to new interest especially in volcanic bromine chemistry and its impact on atmospheric processes. The BrO detection came along with advances in volcanic remote sensing techniques, in particular, robust DOAS applications and the possibility of continuous measurements by automated instruments located at safe distances from the volcano. As one of the consequences, the volcanic community developed an increased interest to use BrO/SO2 ratios as a potential tracer of volcanic activity. BrO is a secondary volcanic gas, but the only bromine species in volcanic plumes, which has been measured by remote sensing techniques today. For a better understanding on bromine chemistry in volcanic plumes and to gain information on the original amount of emitted bromine by only measuring BrO, additional techniques were developed (alkaline traps, diffusion denuders) and adapted for drone-based sampling to determine further gaseous bromine species (i.e. Br2, HBr, HOBr, interhalogens) at various plume ages. Additionally models of plume-atmospheric chemistry were developed to help the interpretation of field-measurements. Model studies simulating plume conditions indicated that a complex atmospheric chemistry mechanism transforms emitted HBr into BrO and other reactive bromine species such as BrOH, Br2, BrCl, BrONO2 or BrNO2. To reproduce the very rapid formation of BrO observed in volcanic plumes, the volcanic emission input to the (low-temperature) plume chemistry models also needs to consider the high-temperature near-vent plume conditions, as represented by thermodynamic models. The formation of BrO and other reactive bromine species depend not only on the amount of bromine emitted but also on plume mixing processes, relative humidity, and aerosol particle acidity. However, uncertainties remain in the validation of the plume chemistry models by a lack of field-measurements. This review provides an overview on volcanic bromine data achieved from established and cutting edge measurement techniques as well as their treatment and interpretation in recent model experiments.
Gesehen am 15.08.2019